ANALISIS WACANA KRITIS OPINI “KAMU BUKAN PEMALAS, KAMU ADALAH PENAKUT” DI MEDIUM DENGAN MODEL VAN DIJK - Lubis, Miranda Putri Madina; Baroroh, Hilma Erfiani (Bahtera Indonesia, 2026)
This study aims to uncover the role of fear as the primary factor behind procrastination by analyzing the opinion piece Kamu Bukan Pemalas, Kamu Adalah Penakut written by Bagus Ramadhan on Medium. The background of this research stems from societal perceptions that often associate procrastination with laziness, without considering other psychological factors. This study employs a qualitative descriptive method with a critical discourse analysis model based on Teun A. Van Dijk's theory, encompassing macrostructure, superstructure, microstructure, social context, and social cognition analysis. The findings reveal that the text deconstructs the laziness stereotype and offers a new perspective on fear as a cause of procrastination. This research contributes to the social and psychological understanding of human behavior and provides new insights into factors influencing individual productivity.